Green synthesis of copper oxide nanoparticles using gum karaya as a biotemplate and their antibacterial application - Thekkae Padil, Vinod Vellora; Černík, Miroslav (International journal of nanomedicine, 2013)
BACKGROUND: Copper oxide (CuO) nanoparticles have attracted huge attention due to catalytic, electric, optical, photonic, textile, nanofluid, and antibacterial activity depending on the size, shape, and neighboring medium. In the present paper, we synthesized CuO nanoparticles using gum karaya, a natural nontoxic hydrocolloid, by green technology and explored its potential antibacterial application. METHODS: The CuO nanoparticles were synthesized by a colloid-thermal synthesis process. The mixture contained various concentrations of CuCl2 • 2H2O (1 mM, 2 mM, and 3 mM) and gum karaya (10 mg/mL) and was kept at 75°C at 250 rpm for 1 hour in an orbital shaker. The synthesized CuO was purified and dried to obtain different sizes of the CuO nanoparticles. The well diffusion method was used to study the antibacterial activity of the synthesized CuO nanoparticles. The zone of inhibition, minimum inhibitory concentration, and minimum bactericidal concentration were determined by the broth microdilution method recommended by the Clinical and Laboratory Standards Institute. RESULTS: Scanning electron microscopy analysis showed CuO nanoparticles evenly distributed on the surface of the gum matrix. X-ray diffraction of the synthesized nanoparticles indicates the formation of single-phase CuO with a monoclinic structure. The Fourier transform infrared spectroscopy peak at 525 cm(-1) should be a stretching of CuO, which matches up to the B2u mode. The peaks at 525 cm(-1) and 580 cm(-1) indicated the formation of CuO nanostructure. Transmission electron microscope analyses revealed CuO nanoparticles of 4.8 ± 1.6 nm, 5.5 ± 2.5 nm, and 7.8 ± 2.3 nm sizes were synthesized with various concentrations of CuCl2 • 2H2O (1 mM, 2 mM, and 3 mM). X-ray photoelectron spectroscopy profiles indicated that the O 1s and Cu 2p peak corresponding to the CuO nanoparticles were observed. The antibacterial activity of the synthesized nanoparticles was tested against Gram-negative and positive cultures. CONCLUSION: The formed CuO nanoparticles are small in size (4.8 ± 1.6 nm), highly stable, and have significant antibacterial action on both the Gram classes of bacteria compared to larger sizes of synthesized CuO (7.8 ± 2.3 nm) nanoparticles. The smaller size of the CuO nanoparticles (4.8 ± 1.6 nm) was found to be yielding a maximum zone of inhibition compared to the larger size of synthesized CuO nanoparticles (7.8 ± 2.3 nm). The results also indicate that increase in precursor concentration enhances an increase in particle size, as well as the morphology of synthesized CuO nanoparticles.
Keywords: velikost částic; Karaya Gum; Particle Size; XRD; CuO nanoparticles; měď; FTIR; XPS; difrakce rentgenového záření; technologie zelené chemie; X-Ray Diffraction; gum karaya; transmisní elektronová mikroskopie; Green Chemistry Technology; Microscopy, Electron, Transmission; Staphylococcus aureus; antibacterial activity; Nanotechnology; Microbial Sensitivity Tests; Anti-Bacterial Agents; spektroskopie infračervená s Fourierovou transformací; nanotechnologie; kovové nanočástice; Metal Nanoparticles; Copper; mikrobiální testy citlivosti; antibakteriální látky; Spectroscopy, Fourier Transform Infrared; Escherichia coli; guma karaya